Paradigm shift in Parkinson's disease: using continuous telemonitoring to improve symptoms control. Results from a 2-years journey - Konitsiotis, Spyridon; Alexoudi, Athanasia; Zikos, Panagiotis; Sidiropoulos, Christos; Tagaris, George; Xiromerisiou, Georgia; Tsamis, Konstantinos; Kostikis, Nicholas; Kanellos, Foivos; Ntanis, Adamantios; Kontaxis, Spyridon; Rigas, George (Frontiers in Neurology, 2024)
Introduction Conventional care in Parkinson's disease (PD) faces limitations due to the significant time and location commitments needed for regular assessments, lacking quantitative measurements. Telemonitoring offers clinicians an opportunity to evaluate patient symptomatology throughout the day during activities of daily living. Methods The progression of PD symptoms over a two-year period was investigated in patients undergoing traditional evaluation, supplemented by insights from ambulatory measurements. Physicians integrated a telemonitoring device, the PDMonitor®, into daily practice, using it for informed medication adjustments. Results Statistical analyses examining intra-subject changes for 17 subjects revealed a significant relative decrease of −43.9% in the device-reported percentage of time spent in “OFF” state (from 36.2 to 20.3%). Following the 24-month period, the majority of the subjects improved or exhibited stable symptom manifestation. In addition to positively impacting motor symptom control, telemonitoring was found to enhance patient satisfaction about their condition, medication effectiveness, and communication with physicians. Discussion Considering that motor function is significantly worsened over time in patients with PD, these findings suggest a positive impact of objective telemonitoring on symptoms control. Patient satisfaction regarding disease management through telemonitoring can potentially improve adherence to treatment plans. In conclusion, remote continuous monitoring paves the way for a paradigm shift in PD, focusing on actively managing and potentially improve symptoms control.